Predições de valores genéticos e ganhos com a seleção entre e dentro de progênies de meio-irmãos e irmãos completos de cajueiro-anão - Sousa, Tomil Ricardo Maia de (2018)
The genetic improvement program of the dwarf cashew tree aims to provide the market with cultivars of high agronomic potential. For this, in the initial phase, progeny tests involving half-siblings and complete siblings are carried out. However, most of the time, this process is hampered by the loss of information during the conduct of the experiments and by the fact that it is necessary to simultaneously consider the evaluation of several characters. Thus, the objective of this study was to identify progenies of half-sibs (PMI) and complete sibs (ICP) of dwarf cashews with agronomic potential and genetically superior individuals within these progenies to subsidize the final stage of the breeding program, comparing the genetic gains generated by selection in PMI and PIC. Seven potatoes and 23 PMI of dwarf cashews were evaluated in three years for plant height (AP) and crown diameter (DC), and in four harvests, the productivity of chestnut (PROD), medium mass (MMC), percentage of nuts (PCF) and chestnut reaction to powdery mildew (RCO), in the randomized block design, with information from individuals collected from within the plots. In order to obtain the variance components and genetic parameter estimates, the Restricted Maximum Likelihood / Best Nonlinear Predictor (REML / BLUP) method was used. Predictions of genetic values revealed that the selection performed between and within PMI and PIC consisted of an excellent strategy for the identification of genetically superior individuals. In the progenies of midwives MI 07-16, MI 07-3 and MI 07-8 and complete sibs IC 07-4 and IC 07-6, individuals with high genetic potential were identified from the application of the selection index genetic algorithm adopted for simultaneous selection. The gains with the practiced selection in PMI of dwarf cashew were higher than those obtained with the selection in PIC. Individuals such as 386, 112, 183, 1164 and 3144, observed in the PMI experiment, and 343, 342, 461, 344 and 262, in PIC, will be indicated to compose the competition assays of clones of the breeding program.